2007
DOI: 10.1038/sj.ki.5002564
|View full text |Cite
|
Sign up to set email alerts
|

Thiazide-induced subtle renal injury not observed in states of equivalent hypokalemia

Abstract: Hydrochlorothiazide (HCTZ) is used to manage hypertension and heart failure; however, its side effects include mild hypokalemia, metabolic abnormalities, and volume depletion, which might have deleterious effects on renal and endothelial function. We studied whether HCTZ cause renal injury and/or altered vasoreactivity and if these changes are hypokalemia-dependent. Rats were given a normal diet or a diet moderately low in potassium K+ with or without HCTZ. Animals fed either a low K+ diet alone or HCTZ develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 49 publications
2
40
2
Order By: Relevance
“…For all CKD subtypes, the hypertension guidelines from the National Kidney Foundation Kidney Disease Outcomes Quality Initiative (36) recommend diuretics along with RAS axis inhibitors to lower BP and reduce risk for CVD. Our findings support this approach and allay concerns about long-term consequences of renal injury induced by thiazide diuretics in animal models (37). Finally, the high cardiovascular event rate associated with CKD in our study underscores the need for research into novel preventive and treatment strategies for CVD in CKD (38).…”
Section: 49supporting
confidence: 78%
“…For all CKD subtypes, the hypertension guidelines from the National Kidney Foundation Kidney Disease Outcomes Quality Initiative (36) recommend diuretics along with RAS axis inhibitors to lower BP and reduce risk for CVD. Our findings support this approach and allay concerns about long-term consequences of renal injury induced by thiazide diuretics in animal models (37). Finally, the high cardiovascular event rate associated with CKD in our study underscores the need for research into novel preventive and treatment strategies for CVD in CKD (38).…”
Section: 49supporting
confidence: 78%
“…These Aldo concentrations, while not entirely physiologic, have been observed and even exceeded in adrenally intact but stimulated animals (24). In other animal models, even more modest interventions like daily diuretic administration have been shown to increase Aldo levels between two and three times those observed in controls (30,37). Reungjui and co-workers (37) showed that administration of the diuretic hydrochlorothiazide over a period of 20 wk was associated with a twofold increase in Aldo concentration and fibrotic changes within the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…In other animal models, even more modest interventions like daily diuretic administration have been shown to increase Aldo levels between two and three times those observed in controls (30,37). Reungjui and co-workers (37) showed that administration of the diuretic hydrochlorothiazide over a period of 20 wk was associated with a twofold increase in Aldo concentration and fibrotic changes within the kidney. Thus, such "supraphysiologic concentrations" of Aldo are achievable in vivo and overtime, they appear to play a role in the fibrotic process.…”
Section: Discussionmentioning
confidence: 99%
“…The HR remained relatively constant adjusting for these factors, and there was little evidence that these factors explained the increased risk for CKD. Further studies are needed to determine whether the risk for CKD in community stone formers is related to medications (e.g., thiazide diuretics [31,32], citrate [33], analgesic nephropathy), stone type (8), urinary tract infections (34), shock wave lithotripsy (35,36), recurrent obstruction with high stone burden (37), or damage from chronic crystalluria (particularly calcium oxalate) (26).…”
Section: Discussionmentioning
confidence: 99%